POPULATION GENETICS OF THE SPRUCE BUDWORM, CHORISTONEURA FUMIFERANA(CLEM.) FREEMAN (LEPIDOPTERA: TORTRICIDAE), IN RELATION TO GEOGRAPHICAL AND POPULATION DENSITY DIFFERENCES - Harvey, G.T. (The Canadian Entomologist, 1996)
Abstract Collections (68) of spruce budworm from 33 locations from Newfoundland to Alaska were analysed for isozyme frequencies using horizontal starch gels. Collections represented pre-, early-, mid-, late-, and post-outbreak stages of several populations in balsam fir, white spruce, and mixed host forests, as well as successive annual collections at several locations. Isozymes were measured at 11 loci in mature larvae and at six loci in pheromone-trapped males; frequencies were essentially the same in both stages, and from all host species. Three loci (IDH-2, LDH-1, and AAT-1) were found to be sex-linked, with no heterozygotes in females. Mean percentage heterozygosity ranged from 13.2 to 23.1; at individual locations it tended to decrease over successive years of outbreak and over successive collections in the same year. Contingency chi-square analysis indicated small differences related to location and outbreak history but all populations were generally homogeneous over the entire range. Nevertheless, one allozyme of AAT-1 exhibited a significant cline in frequency from the southeast to the northwest. Gene flow across the entire range appeared to be appreciable.